Strengthening linkages between home, school and community for the health and total development of Caribbean children and youth - Pan American Health Organization. Caribbean Program Coordination (PAHO Office of Caribbean Programme Coordination)
This handbook provides guidelines for strengthening home-school-community linkages in the Caribbean.
Prepared under the School Health and Family Life Education Project, sponsored by Carnegie Corporation of New York and the Pan American Health Organization (Office of the Caribbean Program Coordination) Note: no date of issue indicated in the document
Keywords: health and family life education; youth development